2016
DOI: 10.1039/c6ra09127j
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic supports based on biomorphic SiC for the catalytic combustion of hydrogen

Abstract: Application of biomorphic porous SiC monoliths as Pt catalysts supports for the catalytic combustion of hydrogen. Anisotropic thermal behaviour is highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…were calculated (Table 3). The dealloyed Low Pt-Cu_He sample has the lowest AAE of the three (1kJ.mol -1 ), followed by the (as supporting information) show a certain activation upon cycling, demonstrating that the catalyst is durable, as expected for a Pt catalyst under oxidizing conditions [6][7][8].…”
Section: Dealloyed Samplesmentioning
confidence: 63%
See 1 more Smart Citation
“…were calculated (Table 3). The dealloyed Low Pt-Cu_He sample has the lowest AAE of the three (1kJ.mol -1 ), followed by the (as supporting information) show a certain activation upon cycling, demonstrating that the catalyst is durable, as expected for a Pt catalyst under oxidizing conditions [6][7][8].…”
Section: Dealloyed Samplesmentioning
confidence: 63%
“…Due to its relative simplicity it can be considered as model catalytic oxidation reaction in the gas phase, and has applications in heaters for domestic or industrial use (for example, cooking, heating spaces, floors and walls, drying and other heating industrial processes) or in safety devices [1][2][3][4][5]. H2 (g) + ½ O2 (g) → H2O (g) (1) Regarding safety applications, the CHC can be employed as a controllable means to eliminate the undesired amounts of hydrogen in installations such as in the nuclear industry or fuel cell-based power generation devices [3][4][5][6][7][8]. The elimination of residual hydrogen from the exhaust gases from fuel cells requires the use of catalysts that are active at room temperature (RT).…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic combustion of H 2 is used for heat production but it can also be utilized when unwanted H 2 needs to be removed, especially in closed spaces with limited ventilation. The properties of H 2 , such as its low density, wide flammability range, and low ignition energy, increases the probability of a fire hazard in any situation where H 2 is present .…”
Section: Passive Autocatalytic Recombinersmentioning
confidence: 99%
“…Any situation were H 2 can be accidently released and accumulate, to possibly explode, needs these countermeasures for safe operation . The amounts of H 2 that need to be eliminated can vary, from large amounts generated in nuclear accidents, for example, to exhaust gases from fuel cells …”
Section: Passive Autocatalytic Recombinersmentioning
confidence: 99%
“…For instance, it has been found that the high surface area and elongated nature of the porosity makes bioSiCp an interesting catalyst carrier, especially for high temperature reactions such as partial oxidation of methane to syngas [106], cellulose conversion to hydrogen [107] using Ni particles, or catalytic combustion of hydrogen [108] but also combined with zeolites to form structured monoliths for sorption and catalysis [109,110].…”
Section: Applicationsmentioning
confidence: 99%